Biotechnological and biomedical applications of mesenchymal stem cells as a therapeutic system. (17th February 2016) - Rahimzadeh, Amirbahman; Tabatabaei Mirakabad, Fatemeh Sadat; Movassaghpour, Aliakbar; Shamsasenjan, Karim; Kariminekoo, Saber; Talebi, Mehdi; Shekari, Abolfazl; Zeighamian, Vahideh; Gandomkar Ghalhar, Masoud; Akbarzadeh, Abolfazl
Abstract : Mesenchymal stem cells (MSCs) are non-hematopoietic, multipotent progenitor cells which reside in bone marrow (BM), support homing of hematopoietic stem cells (HSCs) and self-renewal in the BM. These cells have the potential to differentiate into tissues of mesenchymal origin, such as fibroblasts, adipocytes, cardiomyocytes, and stromal cells. MSCs can express surface molecules like CD13, CD29, CD44, CD73, CD90, CD166, CXCL12 and toll-like receptors (TLRs). Different factors, such as TGF-β, IL-10, IDO, PGE-2, sHLA-G5, HO, and Galectin-3, secreted by MSCs, induce interaction in cell to cell immunomodulatory effects on innate and adaptive cells of the immune system. Furthermore, these cells can stimulate and increase the TH2 and regulatory T-cells through inhibitory effects on the immune system. MSCs originate from the BM and other tissues including the brain, adipose tissue, peripheral blood, cornea, thymus, spleen, fallopian tube, placenta, Wharton's jelly and umbilical cord blood. Many studies have focused on two significant features of MSC therapy: (I) MSCs can modulate T-cell-mediated immunological responses, and (II) systemically administered MSCs home in to sites of ischemia or injury. In this review, we describe the known mechanisms of immunomodulation and homing of MSCs. As a result, this review emphasizes the functional role of MSCs in modulating immune responses, their capability in homing to injured tissue, and their clinical therapeutic potential.